Retraction Note: Ruqyah and Its Use among Patients with Cancer - Çaksen, Hüseyin (Journal of Child Science, 2023)
The above article published in Journal of Child Science in Volume 13, Number 01, e20–e27, on March 20, 2023 (DOI: 10.1055/s-0043-1764498), has been retracted as it is lacking scientific base.